Using the Diversity of Lichens in Maribu Forest Area, West Sentani District, Jayapura Regency as a Baseline Data on Environmental Changes - Suharno Suharno; Hasifa Hasifa; Supeni Sufaati (Jurnal Ilmu Kehutanan, 2024)
Lichens are thallophytes, capable of absorbing water, nutrients, and chemical compounds in the air, which led to their application as bio-indicators of air quality. Therefore, this research aimed to determine the abundance and diversity of lichens in the Maribu Village, West Sentani District, Jayapura Regency. This research used the exploration method by tracing the observation paths for vegetation and the presence of lichens. This research established three observation stations with three observation plots of 5 m × 5 m in each station. The obtained samples were identified in the Biology Laboratory of FMIPA Cenderawasih University. This research identified 14 tree species belonging to 12 families and 22 species of lichens belonging to 10 families in the observation plots. Phlyctis argena (39 colonies) and Cryptothecia striata (32 colonies) had the highest colony and fell in the 'very common' category, with the diversity index value (H') of 2.79, which was in the medium category status. The results became the first recorded data in the lowland areas of Papua and could become a baseline for further research.